Revision of Multiple Revised Hinge Total Knee Replacement -a Rare Case Report - Muthusaravanakumar Meignanagure; Yogadeepan Dhakshinamurthi; Sathyamoorthy S.Elangovan; Ganesh Ramesh Shetty (Journal of Orthopaedic Case Reports)
Introduction: Revision total knee replacements are very common now a days. Most common causes include early total knee replacement and increased life expectancy. Proper pre-operative planning and assessment are crucial for the appropriate management of revision cases. Case Report: An 83-year-old gentleman came with a history of right knee pain and instability for past 1 year. He underwent bilateral TKR 20 years back, after which he underwent two revisions for his right knee 5 and 10 years following the first surgery. Intraoperatively, femoral and tibial components were found stable, and only poly wear was noted with hinge breakage and cement mantle interposition; hence, only hinge revision was done. Conclusion: Not all cases of revision need complete component replacement. Addressing intraoperative findings and appropriate management prevents complications.